Pacus Piaractus mesopotamicus alimentados com dietas suplementadas com vitaminas C e E, submetidos ao desafio por Aeromonas hydrophila - Garcia, Fabiana [UNESP] (2005)
The present work evaluated the effects of exogenous cortisol and fish size in the susceptibility for Aeromonas hydrophila infection in Piaractus mesopotamicus. Four bacteria concentrations (zero; 6x106; 6x107 and 6x108 cfu/mL) were tested in fish injected or not with 0.04 mg of cortisol/body weight 24 hours before bacteria inoculation. Fish were divided in two groups by weight, ranging from 15 to 25g and from 30 to 40g, occupying 16 tanks with six fish each. Cortisol was injected intraperitoneally on the left side of fish abdomen. Aeromonas hydrophila inoculums were diluted in saline solution to reach the expected concentrations. Bacteria were injected intraperitonially on the right side of the abdomen, therefore, it was possible to identify any lesions caused by both injections. Mortality and clinical signs were observed every 12 hours during seven days. Necropsy was performed as soon as possible in dead fish, and in all of survivor fish at the end of the test. Exogenous cortisol applications and fish size did not present influence in the occurrence of clinical signs, as well only fish inoculated with the highest bacteria concentration showed a small hemorrhagic lesion in the injection point, independently of size and presence of exogenous cortisol. Fish that received the two highest concentrations of bacteria showed hemorrhagic abdominal cavity. Only the highest bacteria concentration caused death of the animals during the experiment. It was possible to observe the influence of cortisol and fish size in the susceptibility to A. hydrophila hence the higher mortality occurs faster in small fish that received the cortisol injection